Betvily: Pendampingan kemandirian ekonomi pemuda desa melalui e-commerce di Kecamatan Wonosalam Demak - Saifudin, Saifudin (Nur Science Institute, 2024)
Massive urbanization in Indonesia has led to increased poverty in rural areas. This community service aims to address this problem by developing the Betvily e-commerce mentoring program for village youth in Wonosalam District. The participants are young people interested in developing businesses through digital platforms. This community service will evaluate the program’s effectiveness in improving digital literacy, developing entrepreneurial skills, and increasing the income of village youth. In addition, it will also identify obstacles and challenges faced in implementing the program and formulate recommendations for the development of similar programs in the future. The impact of this community service is that young people in Wonosalam District gain knowledge and skills in utilizing digital technology to market their products through e-commerce platforms. The results of this program show an increase in the capacity of village youth to use technology for business development, which has the potential to encourage strengthening the local economy. The Betvily program is expected to be a sustainable model for empowering village communities in the digital era.